Challenges in Teaching English as A Foreign Language in Indonesia - Adela Putri; Leza Marcella; Sri Wahyuni (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Teaching English as a Foreign Language (EFL) in Indonesia faces various challenges that affect learning effectiveness and student achievement. This article explores major issues related to students, teachers, instructional practices, technology, sociocultural factors, and educational policies. Many students experience difficulties due to limited exposure to English, low motivation, language anxiety, and differing proficiency levels. Teacher-related challenges include limited professional competence, large class sizes, and the continued use of traditional teaching methods. The development of educational technology, particularly Artificial Intelligence (AI), offers opportunities to enhance language learning, although unequal access, limited digital literacy, and academic integrity issues remain concerns. Sociocultural barriers, such as fear of making mistakes and lack of confidence, also reduce student participation in communicative activities. Addressing these challenges requires collaboration among teachers, institutions, policymakers, and learners through professional development, improved resources, student-centered learning, and responsible technology integration to strengthen English language education in Indonesia.